2013
DOI: 10.1016/j.ajpath.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Fibrocyte-Like Cells from Intrauterine Growth Restriction Placentas Have a Reduced Ability to Stimulate Angiogenesis

Abstract: Intrauterine growth restriction (IUGR) is a common complication of pregnancy whereby the fetus fails to achieve its genetic growth potential. Malformation of the placental vasculature is observed in IUGR and may be due to the development of the placenta in a chronically hypoxic environment. Recently, we identified that the predominant stromal cells in the angiogenic zones of the placenta are fibrocyte-like cells. The conditioned medium from fibrocyte-like cells (FcCM) has been shown to stimulate angiogenesis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Abnormal vasculogenesis and angiogenesis are correlated with the impaired placental and fetal development observed in complicated pregnancies, such as IUGR [20]. Interestingly, in vitro studies showed that IUGR placental villous stromal cells altered ability to stimulate endothelial tubule-like structure formation and migration [37]. In addition, the imbalance between pro-and antiangiogenic factors is well documented in placentas and in maternal blood of IUGR and PE pregnancies, suggesting a role in their pathophysiology [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal vasculogenesis and angiogenesis are correlated with the impaired placental and fetal development observed in complicated pregnancies, such as IUGR [20]. Interestingly, in vitro studies showed that IUGR placental villous stromal cells altered ability to stimulate endothelial tubule-like structure formation and migration [37]. In addition, the imbalance between pro-and antiangiogenic factors is well documented in placentas and in maternal blood of IUGR and PE pregnancies, suggesting a role in their pathophysiology [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…While these methods have provided valuable insights into placental vascular biology, they lack the ability to provide detailed morphology in conjunction with phenotypic and dimensional information. Recent observations suggesting that several cell types within the placenta, including trophoblast cells, macrophages, and stromal cells, function together to promote placental development and angiogenesis [41][42][43] underscore the importance of being able to simultaneously examine all of these critical parameters. Using WMIF, we were able to overcome these limitations and obtain unparalleled images of the morphology, phenotype, and spatial orientation of several placental cell populations, including endothelial cells.…”
Section: Discussionmentioning
confidence: 99%